2015
DOI: 10.14737/journal.aavs/2015/3.12.649.676
|View full text |Cite
|
Sign up to set email alerts
|

Contagious Pustular Dermatitis (Orf Disease) - Epidemiology, Diagnosis, Control and Public Health Concerns

Abstract: | Contagious pustular dermatitis (CPD), also known as Orf or contagious ecthyma is an important viral disease of sheep and goats. It is mainly seen as a benign disease but malignant form has also been reported from few parts of the world. The rates of morbidity and mortality are higher, particularly in lambs and kids experiencing the disease for the first time. The causative agent of disease is Orf virus, type species of the genus Parapoxvirus belonging to family Poxviridae. The virus produces localized persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 104 publications
3
50
0
2
Order By: Relevance
“…In addition, typical lesions can be seen in mouth, nose, oral mucosa, tongue, gingiva and palate. Similar lesions are observed in the lambs as small erythematous and ulcerated papules on the gums, tongue and palate [2,3,5,8,9] . Skin lesions of the disease are frequently seen in the head, face, ears, neck, chest, legs and inguinal region [10] .…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, typical lesions can be seen in mouth, nose, oral mucosa, tongue, gingiva and palate. Similar lesions are observed in the lambs as small erythematous and ulcerated papules on the gums, tongue and palate [2,3,5,8,9] . Skin lesions of the disease are frequently seen in the head, face, ears, neck, chest, legs and inguinal region [10] .…”
Section: Introductionsupporting
confidence: 69%
“…It has also known that the rate of spread of the disease and the size of the lesions are related to the labor exposure which causes injuries on the mouths of animals during grazing [3] . It has been reported by different researchers that the disease affects all age groups equally, without racial and gender discrimination between animals [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general contagious ecthyma will commonly affects animal lips, However mouth and surrounding skin were also harmed, Furthermore the disease can also affect the face, feet and even the udder skin of lactating ewes, As the causative virus will causes superficial sores, which then will crusted and finally scabbing over and then falling down, Moreover, the underlying skin heals without scarring, where, this cycle takes approximately 4-5weeks or maybe less, Thereby lambs lose condition as they are reluctant to eat and it is too painful for ewes to feed suckling lambs, However, those with foot lesions will be lame, Furthermore, these sores may become infected by opportunistic bacteria, causing further infection (Kumar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Infection occurs via direct contact with the virus which is highly resistant and can survive in the environment for more than one year (Constable et al ,2017). The disease occurs most commonly in young lambs, but occasionally in older sheep, Grazing of coarse pastures or stubbles may predispose to infection with scabby mouth as oral abrasions increase the potential for the virus to gain entry (Kumar et al ,2015 ). In Basrah governorate, there was no real document clarify the disease and little information had been provided in sheep, therefore, the main aims of the current study were to study and explore the main clinical manifestations of the disease showed by diseased sheep, and confirmed the diagnosis of the causative virus using molecular method, PCR technique, Moreover to study the hematological changes in diseased animals, Evaluation of acute phase response of diseased animals via evaluation of haptoglobin and Fibrinogen.…”
Section: Introductionmentioning
confidence: 99%